Systematization of methods and tools of operative controlling at enterprise - Rusanovska, О. А. (Видавництво Львівської політехніки, 2014)
The necessity of the operative controlling use at the enterprise has been shown. The difference between operative and strategic controlling has been demonstrated. The essence of operative controlling has been presented and the main tasks, which this concept performs, have been outlined and characterized. The difference between the methods and tools of operative controlling has been investigated, the main ones have been determined. The article has been written with the use of such methods as abstraction, induction and deduction, logical approach, definition and interpretation. The findings consist in the fact that the selected issue of the research is relevant nowadays. As a result of the development of science and technology the operative controlling will face new objectives, while new methods and tools of their realization will appear. Обґрунтовано необхідність застосування оперативного контролінгу на підприємстві. Продемонстровано відмінність між оперативним та стратегічним контролінгом. Наведено сутність оперативного контролінгу та окреслено основні завдання, які виконує ця концепція, охарактеризовано їх. Досліджено відмінність між інструментами та методами оперативного контролінгу, визначено основні з них. У дослідженні застосовано такі методи, як абстрагування, індукція і дедукція, логічний підхід, визначення та інтерпретація. Отримані висновки полягають в тому, що вибрана проблема дослідження є актуальною сьогодні, а внаслідок розвитку науки і техніки перед оперативним контролінгом поставатимуть нові завдання і з’являтимуться нові методи та інструменти їх реалізації.
Систематизація методів та інструментів оперативного контролінгу на підприємстві
Keywords: operative controlling; essence and tasks of operative controlling; methods and tools of operative controlling; оперативний контролінг; сутність та завдання оперативного контролінгу; методи та інструменти (засоби) оперативного контролінгу